A Child with Severe Malaria Presenting with Acute Surgical Abdomen (Duodenal Perforation) - Tika Ram Bhandari; Sudha Shahi; Rajesh Poudel; Nagendra Chaudhary (Hindawi Limited, 2016)
Plasmodium falciparum, the commonest cause of severe malaria in children, is an important cause of mortality in developing nations like Nepal. Duodenal perforation in a case of complicated malaria, although a rare entity, can occur in children. Early diagnosis, proper medical treatment, and early surgical repair can be a lifesaving measure in such cases. Here, we report a case of a 5-year-old male child with falciparum malaria complicated by a duodenal perforation that was successively managed with appropriate antimalarial drugs and early surgical repair.